Welcome Banana in the traditional rice-potato cropping system of Purba Burd - Saha, Poly; Das, Sibsankar; Bera, Soumen; Datta, Jhuma (Indian Horticulture, 2022)
A study was focussed to provide the best alternative to the farmers of Purba Bardhaman, West Bengal who are habituated to trail only rice-potato cropping system. Unremitting monoculture followed by everyone generates several issues like a marketing problem, not to fetch optimum value for the product, etc. Moreover, excessive dependence upon a single crop increases the chance of cumulative crop failure due to natural calamities. To address these problems, a survey was conducted and we came up with an idea for banana cultivation. But before suggesting it to the farmers, a research trial was laid out at Teaching farm, College of Agriculture, Purba Burdwan, BCKV to perceive the performance of bananas in this region. Whilst, we adopted GAP, recorded observation on the disease-pest situation and remedial measures were taken timely. Ultimately, we harvested a good yield for the two consecutive years, and the cost-benefit estimated 1:1.50 which gives us the confidence to encourage the farmers of Purba Burdwan for banana cultivation.